The prediction value of Treg cell subtype alterations for glucocorticoid treatment in newly diagnosed primary immune thrombocytopenia patients. Issue 181 (September 2019) - Cheng, Luya; Liu, Chanjuan; Li, Feng; Wu, Boting; Min, Zhihui; Chen, Pu; Zhan, Yanxia; Ke, Yang; Hua, Fanli; Yuan, Ling; Sun, Lihua; Chen, Hao; et al.
Abstract: Background: Primary immune thrombocytopenia (ITP) is an autoimmune heterogeneous disorder of which Treg cells are numerically or functionally deficient. It is known that human FoxP3 + CD4 + T cells were composed of 3 phenotypically and functionally distinct subpopulations (resting Treg, rTreg; activated Treg, aTreg; and non-suppressive Treg, n-sTreg). The current study was aimed to determine whether these Treg subtypes are altered in ITP patients and the related potential clinical applications. Method: Normal control volunteers and newly diagnosed ITP patients were enrolled in the study. The percentage of Treg cells' subtypes in peripheral blood was examined by flow cytometry before and after the glucocorticoid treatment. The IL-10 production by Treg subtypes was also examined. Results: Treg cell subtypes of aTreg increased, rTreg decreased, and n-s Treg increased in newly diagnosed ITP patients' peripheral blood. The IL-10 production by respective Treg subtype didn't change after the treatment, and aTreg cells had the highest IL-10 yield. Patients who gained remission during follow-up had a higher aTreg cells' percentage than those who did not at the disease diagnosis. Conclusion: Tregs cell subtypes percentage was altered when ITP occurred. The increased aTreg cells at disease diagnosis might predict a better glucocorticoid treatment efficacy. Highlights: Our data suggested that Tregs cell subtypes (rTreg cells; aTreg cells; cytokine secreting Treg cells) percentage was altered when ITP occurred. The increased aTreg cells at disease diagnosis might predict a better glucocorticoid treatment efficacy. The change of Treg subtypes had prediction value for glucocorticoid treatment in newly diagnosed primary ITP patients.